2018
DOI: 10.1128/jvi.00422-18
|View full text |Cite
|
Sign up to set email alerts
|

Role of MxB in Alpha Interferon-Mediated Inhibition of HIV-1 Infection

Abstract: Type I interferon inhibits viruses through inducing the expression of antiviral proteins, including the myxovirus resistance (Mx) proteins. Compared to the human MxA protein, which inhibits a wide range of viruses, the MxB protein has been reported to specifically inhibit primate lentiviruses, including HIV-1, and herpesviruses. Further, the role of endogenous MxB in alpha interferon-mediated inhibition of HIV-1 infection was questioned by a recent study showing that MxB knockout did not increase the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…However, these results show that while MxB does play a role in the IFN-mediated inhibition of VSV-G pseudotyped HIV-1 viruses (compare MxB-KO cells to NTCs in Figure 3D ), this effect is masked by dominant IFITM inhibition of these VSV-G pseudotyped viruses ( Figure 3E ). Similar results have been reported recently elsewhere ( Xu et al, 2018 ). Therefore, viral entry route impacts restriction factor sensitivity and the role of MxB in IFN inhibition of HIV-1 in THP-1s is partially-masked by other ISGs when HIV-1 LAI is pseudotyped by VSV-G.…”
Section: Resultssupporting
confidence: 93%
“…However, these results show that while MxB does play a role in the IFN-mediated inhibition of VSV-G pseudotyped HIV-1 viruses (compare MxB-KO cells to NTCs in Figure 3D ), this effect is masked by dominant IFITM inhibition of these VSV-G pseudotyped viruses ( Figure 3E ). Similar results have been reported recently elsewhere ( Xu et al, 2018 ). Therefore, viral entry route impacts restriction factor sensitivity and the role of MxB in IFN inhibition of HIV-1 in THP-1s is partially-masked by other ISGs when HIV-1 LAI is pseudotyped by VSV-G.…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that MxB does not contribute to the IFN-β sensitivity of the RGDA/Q112D virus in T cells, and these findings are similar to those of previous studies that suggested a limited role of MxB in restriction mediated by type I IFN in myeloid THP-1 cells (10, 61). During preparation of the manuscript for this article, Xu et al argued that the limited role of MxB reported previously was due to experimental conditions with HIV-1 carrying the VSV G protein (62). It should be noted that our results were obtained with replication-competent viruses harboring HIV-1 Env (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, HIV-1 core stability and uncoating are also tightly regulated via the interactions between CA and various cellular factors to enable most post entry steps such as cytoplasmic trafficking, nuclear entry, integration, and host restriction 12 , 21 . CA-interacting host factors include TRIM5 α 22 , 23 , cleavage and polyadenylation specific factor 6 (CPSF6) 24 , 25 , nucleoporins 153 26 , 27 , 28 and 358 29 , 30 (NUP153 and NUP358), MxB 31 , 32 , and cyclophilin A 33 , 34 , 35 . Therefore, in addition to potentially inhibiting viral strains resistant to current drug classes, CA-targeting small molecules also have the advantage of conferring both early stage and late stage antiviral phenotypes by disrupting CA‒CA and CA‒host interactions.…”
Section: Introductionmentioning
confidence: 99%